2021
DOI: 10.19184/bioedu.v19i2.25579
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Application Based Android to Develop the Knowledge of Plant Identification for Biology Education College Student

Abstract: Plant identification is a process of determining plant species based on classification system by observing either morphological structure or anatomical structure of the plant. The aim of this study for determine the effect of using applications on the ability to identify plants for biology education college students by comparing the identification abilities of students after carrying out plant identification activities using matching plant the characteristic of object methods and application based android. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Activities utilizing the PlantNet mobile application provide more permanent information about plant species than computer‐based digital herbarium activities (Iskrenovic‐Momcilovic, 2020 ). As a result of plant identification activities conducted with PlantNet, it was observed that students' plant identification skills improved significantly (Santri et al., 2021 ), and a significant improvement was observed in students' awareness and levels of concern about environmental problems (Álvarez‐Herrero, 2023 ). Secondary school students used PlantNet, traditional image‐based printed identification keys, and unstructured searches on the Internet to identify plants and stated that PlantNet was the least difficult of these methods (Lang & Šorgo, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activities utilizing the PlantNet mobile application provide more permanent information about plant species than computer‐based digital herbarium activities (Iskrenovic‐Momcilovic, 2020 ). As a result of plant identification activities conducted with PlantNet, it was observed that students' plant identification skills improved significantly (Santri et al., 2021 ), and a significant improvement was observed in students' awareness and levels of concern about environmental problems (Álvarez‐Herrero, 2023 ). Secondary school students used PlantNet, traditional image‐based printed identification keys, and unstructured searches on the Internet to identify plants and stated that PlantNet was the least difficult of these methods (Lang & Šorgo, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, high school students identified the PlantNet application as a successful tool for identifying plant species, and it was observed that they had learned more as a result of this activity (Muchsin et al., 2021 ). Meanwhile, it was emphasized that the taxonomy of some plants does not correspond to their actual names in PlantNet identifications, and therefore users should be more cautious when identifying plant species with PlantNet (Santri et al., 2021 ). Although the students chose PlantNet as the method with which they encountered the fewest difficulties in plant identification, they indicated that books would be their future method of choice for species identification (Lang & Šorgo, 2022 ).…”
Section: Introductionmentioning
confidence: 99%